2020
DOI: 10.1140/epjb/e2020-10111-9
|View full text |Cite
|
Sign up to set email alerts
|

Vibrational and magnetic signatures of extended defects in Fe

Abstract: Defects change the phonon spectrum and also the magnetic properties of bcc-Fe. Using molecular dynamics simulation, the influence of defects – vacancies, dislocations, and grain boundaries – on the phonon spectra and magnetic properties of bcc-Fe is determined. It is found that the main influence of defects consists in a decrease of the amplitude of the longitudinal peak, PL, at around 37 meV. While the change in phonon spectra shows only little dependence on the defect type, the quantitative decrease of PL is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 62 publications
0
7
0
Order By: Relevance
“…The change in P L is considerably more pronounced in the simulated sample than in experiment; we consider that this is due to the larger grain size of the experimental sample. In previous work [8], it was shown that the P L decrease correlates linearly with an increase in dislocation density in the material.…”
Section: Resultsmentioning
confidence: 86%
See 4 more Smart Citations
“…The change in P L is considerably more pronounced in the simulated sample than in experiment; we consider that this is due to the larger grain size of the experimental sample. In previous work [8], it was shown that the P L decrease correlates linearly with an increase in dislocation density in the material.…”
Section: Resultsmentioning
confidence: 86%
“…To analyze and interpret the changes of the pDOS under strain, we calculate data for the pDOS of Fe using molecular dynamics simulation.These data were obtained in a way as described in [8] for a polycrystalline (pc) Fe sample with a grain size of around 10 nm; the sample contains around N = 250,000 atoms. The strained sample was produced with a strain rate of 10 10 s −1 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations